2023
DOI: 10.1186/s12967-023-04054-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, longitudinal analysis of the gut microbiome in patients with locally advanced rectal cancer predicts response to neoadjuvant concurrent chemoradiotherapy

Abstract: Background Neoadjuvant concurrent chemoradiotherapy (nCCRT) is a standard treatment for locally advanced rectal cancer (LARC). The gut microbiome may be reshaped by radiotherapy through its effects on microbial composition, mucosal immunity, and the systemic immune system. We sought to clarify dynamic, longitudinal changes in the gut microbiome and blood immunomodulators throughout nCCRT and to explore the relationship of such changes with outcomes after nCCRT. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Preoperative neoadjuvant chemoradiotherapy was an important part of rectal cancer treatment ( 28 ), and many previous studies had reported prediction models for the response of rectal cancer to preoperative neoadjuvant therapy ( 18 , 29 , 30 ). However, cases of progression after preoperative neoadjuvant therapy could not be ignored.…”
Section: Disscussionmentioning
confidence: 99%
“…Preoperative neoadjuvant chemoradiotherapy was an important part of rectal cancer treatment ( 28 ), and many previous studies had reported prediction models for the response of rectal cancer to preoperative neoadjuvant therapy ( 18 , 29 , 30 ). However, cases of progression after preoperative neoadjuvant therapy could not be ignored.…”
Section: Disscussionmentioning
confidence: 99%